Ecosystem collaboration for climate action: a case study of the ILCA Project - Ancuța Agheniței; Carmen Nastase; Carmen Chașovschi (Cactus)
In recent years, the number of initiatives dealing with climate change has increased significantly as human activity releases more and more greenhouse gases into the environment. There is no doubt that the effects of these emissions are numerous and increasingly alarming. Against this background, this paper assumes that climate change requires the engagement of various groups of stakeholders. This engagement is referred to in this paper as ecosystem cooperation for climate action. A feature of ecosystem cooperation is the potential to create a multistakeholder network of new partnerships that can generate innovative solutions to climate change problems. This paper argues that ecosystem collaboration is particularly important for both preventing and responding to climate change. Following a theoretical explanation of the concept of ecosystem collaboration, a case study on climate change and sustainability is presented. This case study highlights best practise examples within a European project entitled “Innovation Laboratories for Climate Actions” (ILCA). Through a consortium of six universities and three research institutes from different European countries, the ILCA project aimed to engage multiple stakeholders in national, regional and local ecosystems to develop innovative solutions to tackle climate change. The project brought together businesses, public administrations, civil society and academia from each country. The findings of this paper emphasise the importance of the ILCA project in tackling climate change through ecosystem collaboration and the establishment of a ‘Climate Innovation Lab’ at the Stefan cel Mare” University in Suceava. Such a lab brings together experts from different fields such as economics, engineering and medicine to find innovative solutions to climate problems. We also emphasise the active role of innovation in helping tourism businesses to adapt to climate change. Innovation and collaboration are crucial to fostering a cooperative environment in relation to climate change mitigation.